The Accessibility of Financing for Small Enterprises in the Precious Minerals Jewellery Manufacturing Sector - Mokgadi, Phele Marilyn Senaba; Lubbe, Sam; Soam, Henry Mynhardt (Technium Social Sciences Journal, 2025)
Purpose The purpose of the study was to rigorously examine the accessibility of formal or external financial assistance for small enterprises (SEs) in the precious minerals jewellery manufacturing sector, addressing the critical gap where their growth potential is stifled by a lack of adequate financial resources. The ultimate goal was to deliver actionable conclusions and tailored recommendations to inform financiers in the effective design of suitable small company finance scheme models. Design/methodology/approach The research adopted a quantitative research technique coupled with a descriptive study design. The investigation started with a comprehensive review of relevant literature concerning small enterprise finance and sector-specific risks. Data was systematically identified, classified, and modelled using robust statistical methods to ensure reliability. The focus was on gathering empirical evidence regarding application success rates, stringent collateral requirements, perceived risk, and informational asymmetry. Findings/results The research findings revealed several significant and quantifiable barriers to financial access. These constraints largely clustered around issues of stringent collateral demands, a perceived high-risk profile of the SEs by formal lenders, and complex application procedures that are poorly suited to the operational realities of small manufacturers. Practical implications The interpreted data and actionable conclusions are designed to directly inform and guide financiers. They can use these insights to design suitable future small company finance scheme models that foster financial inclusion and help unlock the economic potential of the precious minerals jewellery manufacturing sector. Originality/value The study provides empirical evidence and quantifiable data on specific financing barriers within the niche precious minerals jewellery manufacturing sector. By focusing on friction points like collateral, perceived risk, and informational asymmetry, and delivering tailored recommendations, it offers new insights for developing finance models that are better suited to the operational realities of small firms in this specific industry, thus filling a critical knowledge gap.